Geospatial Mapping of Orthopaedic Surgeons Age 60 and Over and Confirmed Cases of COVID-19. (17th June 2020) - Jella, Tarun K.; Acuña, Alexander J.; Samuel, Linsen T.; Jella, Taral K.; Mroz, Thomas E.; Kamath, Atul F.
Abstract : Background: Although elective surgical procedures in the United States have been suspended because of the coronavirus disease 2019 (COVID-19) pandemic, orthopaedic surgeons are being recruited to serve patients with COVID-19 in addition to providing orthopaedic acute care. Older individuals are deemed to be at higher risk for poor outcomes with COVID-19. Although previous studies have shown a high proportion of older providers nationwide across medical specialties, we are not aware of any previous study that has analyzed the age distribution among the orthopaedic workforce. Therefore, the purposes of the present study were (1) to determine the geographic distribution of U.S. orthopaedic surgeons by age, (2) to compare the distribution with other surgical specialties, and (3) to compare this distribution with the spread of COVID-19. Methods: Demographic statistics from the most recent State Physician Workforce Data Reports published by the Association of American Medical Colleges were extracted to identify the 2018 statewide proportion of practicing orthopaedic surgeons ≥60 years of age as well as age-related demographic data for all surgical specialties. Geospatial data on the distribution of COVID-19 cases were obtained from the Environmental Systems Research Institute. State boundary files were taken from the U.S. Census Bureau. Orthopaedic workforce age data were utilized to group states into quintiles. Results: States with the highest quintile of orthopaedic surgeons ≥60 years of age included states most severely affected by COVID-19: New York, New Jersey, California, and Florida. For all states, the median number of providers ≥60 years of age was 105.5 (interquartile range [IQR], 45.5 to 182.5). The median proportion of orthopaedic surgeons ≥60 years of age was higher than that of all other surgical subspecialties, apart from thoracic surgery. Conclusions: To our knowledge, the present report provides the first age-focused view of the orthopaedic workforce during the COVID-19 pandemic. States in the highest quintile of orthopaedic surgeons ≥60 years old are also among the most overwhelmed by COVID-19. As important orthopaedic acute care continues in addition to COVID-19 frontline service, special considerations may be needed for at-risk staff. Appropriate health system measures and workforce-management strategies should protect the subset of those who are most potentially vulnerable. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.